2017
DOI: 10.1101/gr.228411.117
|View full text |Cite
|
Sign up to set email alerts
|

Slightly deleterious genomic variants and transcriptome perturbations in Down syndrome embryonic selection

Abstract: The majority of aneuploid fetuses are spontaneously miscarried. Nevertheless, some aneuploid individuals survive despite the strong genetic insult. Here, we investigate if the survival probability of aneuploid fetuses is affected by the genome-wide burden of slightly deleterious variants. We analyzed two cohorts of live-born Down syndrome individuals (388 genotyped samples and 16 fibroblast transcriptomes) and observed a deficit of slightly deleterious variants on Chromosome 21 and decreased transcriptome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…We adapted existing methods in adult 9 by replacing stationary cell identities with regulons. By selecting multiple genes that co-define particular regulons as input we significantly reduced selection bias due to strongly deleterious mutations (‘survivorship bias’ 25 ). Regulons driven by pro-neurogenic genes were characterized by the lowest rate of mutated master genes ( Figure ED5b ) with the Foxo4 (#29) and Onecut3 (#18) clusters completely depleted in mutations ( Figure 3a,c ).…”
Section: Resultsmentioning
confidence: 99%
“…We adapted existing methods in adult 9 by replacing stationary cell identities with regulons. By selecting multiple genes that co-define particular regulons as input we significantly reduced selection bias due to strongly deleterious mutations (‘survivorship bias’ 25 ). Regulons driven by pro-neurogenic genes were characterized by the lowest rate of mutated master genes ( Figure ED5b ) with the Foxo4 (#29) and Onecut3 (#18) clusters completely depleted in mutations ( Figure 3a,c ).…”
Section: Resultsmentioning
confidence: 99%
“…According to Popadin et al (44), embryonic selection in DS depends on gene expression. Trisomy 21 fetuses with relatively reduced expression of HSA21 genes might be favored by embryonic selection and thus have a higher probability of being liveborn.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these differences may be encoded on the amplified chromosome, with profound influences on DS severity. A recent study of DS patient genomes identified a dearth of deleterious alleles on sampled chromosome 21, which was inferred to reflect survivor bias in tolerated variants (POPADIN et al 2018). However, the influence of broader genetic background effects has been less clear, as there has been no systematic study exploring the aneuploidy tolerance across genotypes.…”
Section: Introductionmentioning
confidence: 99%